Navy bean supplemented high-fat diet improves intestinal health, epithelial barrier integrity and critical aspects of the obese inflammatory phenotype - Monk, Jennifer M.; Wu, Wenqing; Lepp, Dion; Wellings, Hannah R.; Hutchinson, Amber L.; Liddle, Danyelle M.; Graf, Daniela; Pauls, K. Peter; Robinson, Lindsay E.; Power, Krista A. (The Journal of nutritional biochemistry, 2019)
Obesity is associated with impaired intestinal epithelial barrier function and an altered microbiota community structure, which contribute to host systemic inflammation and metabolic dysfunction. Fiber-rich common beans (Phaseolus vulgaris) promote intestinal health (microbiota and host epithelial barrier integrity) in lean mice. The objective was to assess the intestinal health promoting effects of navy bean supplementation during high-fat (HF)diet-induced obesity. Male C57BL/6 mice were fed either a high-fat (HF) diet (60% of kcal from fat) or an isocaloric HF diet supplemented with 15.7% (by weight) cooked navy bean powder (HF+B) for 12 weeks. Compared to HF, the HF+B diet altered the fecal microbiota community structure (16S rRNA gene sequencing), most notably increasing abundance of Akkermansia muciniphila (+19-fold), whose abundance typically decreases in obese humans and rodents. Additionally, HF+B fecal abundance of carbohydrate fermenting, short chain fatty acid (SCFA) producing Prevotella (+332-fold) and S24–7 (+1.6-fold) and fecal SCFA levels were increased. HF+B improved intestinal health and epithelial barrier integrity versus HF, evidenced by reduced serum fluorescein isothiocyanate (FITC)-dextran concentration in an in vivo gut permeability test, and increased intestinal mRNA expression of tight junction components (ZO-1, occludin), anti-microbial defenses (Reg3γ, IgA, Defα5, Defβ2) and mucins (Muc2). Additionally, HF+B improved the systemic obese phenotype via reduced serum HOMA-IR and leptin:adiponectin ratio, and locally via attenuation of epididymal adipose tissue crown-like structure formation, adipocyte size, and inflammatory transcription factor (NFκBp65 and STAT3) activation. Therefore, navy bean supplementation improved obese intestinal health (microbiota and epithelial barrier integrity) and attenuated the severity of the obese phenotype.